Młodzież i dekomunizacja w ukraińskim Donbasie. Studium etnograficzne - Siegień, Wojciech (Kultura-Społeczeństwo-Edukacja, 2021)
The text, which is part of the new field of social sciences – Donbas Studies, presents partial results of the research carried out in the city of Severodonetsk, which is located in the Lugansk Oblast in Donbas. The author, using the ethnographic method of field research, was looking for an answer to the question of how the process of decommunization in Donbas proceeded, and in particular, how the sense of removing the symbols of communism was negotiated, what aspects of this process turned out to be socially conflicting, and what role young people played in this process? Using the interpretation of metaphors and etymologies, the author states that de-communization in Ukraine, apart from the official imperative of oblivion, brings an element of revenge with it. Thanks to participation in the discussion on the de-communization of young people, it is possible to notice that its field of meaning has been extended to include aspects relating not only to the assessment of the past, but also the current social situation in Ukraine. Thanks to this, de-communization does not only mean an order to forget, but also to remember.